EVALUASI PENERAPAN KEBIJAKAN RESTRUKTURISASI KREDIT DALAM PENYELESAIAN KREDIT MACET PADA KOPERASI SIMPAN PINJAM (KSP) DI KOPERASI PETERNAK GARUT SELATAN (KPGS) CIKAJANG - Alicia Safarina Putri (Indonesian Accounting Literacy Journal, 2022)
Koperasi Peternak Garut Selatan (KPGS) Cikajang is one of the cooperatives experiencing bad credit problems caused by the Covid-19 Pandemic. Many members of the breeder cannot pay the installments because production has decreased and some even have died. In addition, non-breeder members cannot fulfill their installments due to declining economic conditions. One of the steps taken by the Koperasi Peternak Garut Selatan (KPGS) Cikajang is to restructure, so that it is expected to solve credit problems and reduce the level of bad loans. This study aims to determine the implementation of restructuring policies in savings and loan cooperatives in the settlement of bad loans at the Koperasi Peternak Garut Selatan (KPGS) Cikajang. This research was conducted using qualitative methods. The research subject has been determined, namely the savings and loan cooperative Koperasi Peternak Garut Selatan (KPGS) Cikajang. Sources of research data are primary data derived from documentary data in the form of bad credit reports and interviews with KPGS management. The data analysis method used is data reduction, data display, and verification. The results of this study indicate that: 1) The credit restructuring policy at KPGS Cikajang was carried out as an effort to overcome bad loans caused by the covid-19 pandemic. This policy is carried out in the form of extending the tenor and reducing interest arrears. This restructuring policy is applied differently between breeders and non-breeders; 2) The restructuring policy has a profound impact on loan repayment and settlement at KPGS Cikajang.